The decision of wheat farmers to attend some agricultural extension activities in Al-Alam, Salah Al-Din Governorate / Iraq - Haseeb Mahmood Amin (Tikrit Journal for Agricultural Sciences, 2021)
The research aimed to identify the level of farmers ,decisions towards attending some agricultural extension activities in the area of Al-Alam in Salah al-Din Governorate in general, and to identify the level of wheat farmers decisions towards attendance in each of the research fields (the extension meeting, the seminar, the field day), finding the correlation between the level of wheat farmers decisions and each of the independent variables, So the area of Al-Alam was chosen as a region for conducting the research, due to the presence of a large number of wheat farmers, who numbered 704, a random sample of 10% was selected, with size of 70 respondents. The questionnaire was used as a tool to collect data from the respondents, consisting of two parts. The first part included some independent variables and, The second part included(34) standard paragraphs, to measure the level of wheat farmers decisions distributed in three areas, Using three-Level scale (high, medium, weak). The results showed the the study about decision not interest of farmers in the indicative activities directed to them in general, as well in every field of research and found relationship correlation between farmers decisions and the variables studied, which indicates the interest of farmers in their various personal and communicative characteristics in the extension activities. The local extension focuses the content of extension activities on the agricultural crops in which the region is famous as wheat crop and meet the knowledge and skill needs of farmers about serving this crops, which contributes this effectively in their attendance to various extension activities.